O que não pode o empoderado? uma arqueogenealogia do empoderamento em saúde - Conz, Luciana Ribeiro (2017)
In this work we perform an archeogenealogy about Health empowerment. We raise discourses and practices that act in the daily practices of caring for oneself and the other, that encourage certain types of powers and health. The research began by placing Health empowerment as an unknown figure, so that we could defamiliarize with what is supposedly believed about such concept and, from that, investigate its constructions in the health field, as well as its neighborhoods with other fields. From the foucaultian referential of archeogenealogy, we seek to answer the questions: Wich power is this that empowered people should have? Wich people should have power? Wich people should have that power? And who says people should have power? With this methodological horizon, we establish a history of empowerment that does not find its origin or essence, but rather the mistakes, failures and approximations that gave birth and strengthen this concept. Therefore, it was necessary to look at actual statements found in academic articles, booklets of international organizations and public policies. With this movement we were able to apprehend a certain path of empowerment that acts as a technology for the reorganization of health care from a contemporary bio-political and neoliberal axiomatics. It is not only restricted to the conduct of health-illness processes, but also produces care and management of the life that develops and eliminates it within an economic management of oneself and of the population.